Taxonomic relationship among four European Physokermes species (Hemiptera: Coccomorpha) based on nuclear and mitochondrial DNA - Marques, Joana F.; Winde, Inis; Jönsson, Anna Maria; Anderbrant, Olle (Frontiers in Forests and Global Change, 2023)
Introduction Scale insects (Hemiptera: Coccomorpha) feed on a wide variety of agricultural crops and forest and ornamental trees worldwide. These pest insects damage plants not only by causing sap loss but also by reducing the plant's photosynthetic activity. This is because the honeydew they produce acts as a substrate for mold, which covers leaf surfaces. In the last decades, several outbreaks of Physokermes spp. (soft-scale insects) have occurred throughout Europe and have partly been attributed to unusual weather conditions or climate change, as some species seem to be expanding their distribution range. However, the small size of these insects and their large intraspecific morphological variation have hindered the identification of the species responsible for outbreaks. Methods In this study, mitochondrial DNA (cytochrome c oxidase subunit I, COI), ribosomal RNA (28S), and nuclear (elongation factor 1α, EF1α) DNA markers were used to reconstruct the phylogenetic relationships of four Physokermes species sampled throughout Europe in 2013–2015. Results and discussion The results allowed us to clearly distinguish P. hellenicus and P. inopinatus from each other, as these appeared in well-supported clades in the phylogenetic trees and from P. piceae and P. hemicryphys. However, P. hemicryphus appeared in a single clade in trees based on 28S and EF1α but among P. piceae in the COI tree. Further investigations are therefore required to determine the taxonomic status of P. piceae and P. hemicryphys, which seem to comprise a species complex.